Safety and immunogenicity of the rVSV∆G-ZEBOV-GP Ebola virus vaccine candidate in healthy adults: a phase 1b randomised, multicentre, double-blind, placebo-controlled, dose-response study. Issue 8 (August 2017) - Heppner, D Gray; Kemp, Tracy L; Martin, Brian K; Ramsey, William J; Nichols, Richard; Dasen, Emily J; Link, Charles J; Das, Rituparna; Xu, Zhi Jin; Sheldon, Eric A; Nowak, Teresa A; Monath, Thomas P; et al.
Summary: Background: The 2014 Zaire Ebola virus outbreak highlighted the need for a safe, effective vaccine with a rapid onset of protection. We report the safety and immunogenicity of the recombinant vesicular stomatitis virus-Zaire Ebola virus envelope glycoprotein vaccine (rVSV∆G-ZEBOV-GP) across a 6 log10 dose range in two sequential cohorts. Methods: In this phase 1b double-blind, placebo-controlled, dose-response study we enrolled and randomly assigned healthy adults (aged 18–61 years) at eight study sites in the USA to receive a single injection of vaccine or placebo, administered by intramuscular injection. In cohort 1, participants were assigned to receive 3 × 10 3, 3 × 10 4, 3 × 10 5, or 3 × 10 6 PFU doses of rVSV∆G-ZEBOV-GP or placebo. In cohort 2, participants were assigned to receive 3 × 10 6, 9 × 10 6, 2 × 10 7, or 1 × 10 8 PFU doses of rVSV∆G-ZEBOV-GP or placebo. Participants were centrally allocated by the study statistician to vaccine groups or placebo through computer-generated randomisation lists. The primary safety outcome was incidence of adverse events within 14 days in the modified intention-to-treat population (all randomly assigned participants who received vaccine or placebo), and the primary outcome for immunogenicity was IgG ELISA antibody titres at day 28 in the per-protocol population. Surveillance was enhanced for arthritis and dermatitis through to day 56. This study is registered withClinicalTrials.gov, numberNCT02314923 . Findings: Between Dec 26, 2014, and June 8, 2015, 513 participants were enrolled and randomly assigned; one was not immunised because of unsuccessful phlebotomy. In cohort 1, 256 participants received vaccine (3 × 10 3 [n=64], 3 × 10 4 [n=64], 3 × 10 5 [n=64], or 3 × 10 6 PFU [n=64]) and 74 received placebo. In cohort 2, 162 participants received vaccine (3 × 10 6 [n=20], 9 × 10 6 [n=47], 2 × 10 7 [n=47], or 1 × 10 8 PFU [n=48]) and 20 received placebo. Most adverse events occurred in the first day after vaccination, and were mild to moderate in intensity, of a short duration, and more frequent at high vaccine doses (9 × 10 6 PFU and greater). At the 2 × 10 7 PFU dose (used in phase 3 trials), the most common local adverse events versus placebo within the first 14 days were arm pain (57·4% [27 of 47] vs 7·4% [seven of 94]) and local tenderness (59·6% [28 of 47] vs 8·5% [eight of 94]). The most common systemic adverse events at the 2 × 10 7 PFU dose versus placebo, occurring in the first 14 days, were headache (46·8% [22 of 47] vs 27·7% [26 of 94]), fatigue (38·3% [18 of 47] vs 19·1% [18 of 94]), myalgia (34·0% [16 of 47] vs 10·6% [10 of 94]), subjective fever (29·8% [14 of 47] vs 2·1% [two of 94]), shivering or chills (27·7% [13 of 47] vs 7·4% [seven of 94]), sweats (23·4% [11 of 47] vs 3·2% [three of 94]), joint aches and pain (19·1% [nine of 47] vs 7·4% [seven of 94]), objective fever (14·9% [seven of 47] vs 1·1% [one of 94]), and joint tenderness or swelling (14·9% [seven of 47] vs 2·1% [two of 94]). Self-limited, post-vaccination arthritis occurred in 4·5% (19 of 418) of vaccinees (median onset 12·0 days [IQR 10–14]; median duration 8·0 days [6–15]) versus 3·2% (three of 94) of controls (median onset 15·0 days [6–20]; median duration 47·0 days [37–339]), with no apparent dose relationship. Post-vaccination dermatitis occurred in 5·7% (24 of 418) of vaccinees (median onset 9·0 days [IQR 2–12]; median duration 7·0 days [4–9]) versus 3·2% (three of 94) of controls (median onset 5·0 days [3–53]; median duration 33·0 days [5–370]). A low-level, transient, dose-dependent viraemia occurred in concert with early reactogenicity. Antibody responses were observed in most participants by day 14. IgG and neutralising antibody titres were dose-related (p=0·0003 for IgG ELISA and p<0·0001 for the 60% plaque-reduction neutralisation test [PRNT60] by linear trend). On day 28 at the 2 × 10 7 PFU dose, the geometric mean IgG ELISA endpoint titre was 1624 (95% CI 1146–2302) and seroconversion was 95·7% (95% CI 85·5–98·8); the geometric mean neutralising antibody titre by PRNT60 was 250 (176–355) and seroconversion was 95·7% (85·5–98·8). These robust immunological responses were sustained for 1 year. Interpretation: rVSV∆G-ZEBOV-GP was well tolerated and stimulated a rapid onset of binding and neutralising antibodies, which were maintained through to day 360. The immunogenicity results support selection of the 2 × 10 7 PFU dose. Funding: Biomedical Advanced Research and Development Authority, US Department of Health and Human Services.